If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -8w = 10 Solving n + -8w = 10 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8w' to each side of the equation. n + -8w + 8w = 10 + 8w Combine like terms: -8w + 8w = 0 n + 0 = 10 + 8w n = 10 + 8w Simplifying n = 10 + 8w
| 5m^2+30m=-75 | | -10-18= | | [3x-10]=4 | | 3(6-k)+7=-7(k-2)-6 | | 2(2t-4)+t=16t | | 49z^2+28z+53=0 | | 4(7r-7)=-28+8r | | y(y+4)+5=0 | | (3x-3)(3x-3)=16x^2 | | -16x^5-36x^3= | | 4w+4k+m=p | | -7+x=6x-5 | | -3x-24=18+4x | | -5(0.2+0.6)-1.4=0.4 | | 11w-16=3w-11 | | 19+9=n | | -[10z-(19z+8)]=8+(8z+1) | | (4c^2)+4c+1=0 | | -140+16x=12x+36 | | 7.2x-1.7=5.5 | | 5x-2+8=27 | | -4(0.2x+0.6)-1.1=-0.3 | | 12x+18=12x-18 | | 8=8r-1 | | 6x^2+24x-1512=0 | | -19+7x=5(2x-5) | | 2.68d+2.04=-9.5d+6.1 | | 6+2(x-1)=5x+14 | | -5a-5(a-3)=2+3a | | 4x-12=5x+2 | | -8+8x=-7(8-8x) | | 4=-(x-1)+3x+3 |